Strategi Kreatif Humas Dinas Energi Dan Sumber Daya Mineral (Esdm) Provinsi Bengkulu Dalam Pengelolaan Media Sosial - Muhammad Firdaus; Sapta Sari; Dilmai Putra (Jurnal Multidisiplin Dehasen (MUDE), 2024)
This research aims to describe the creative public relations strategy of the Bengkulu Province Department of Energy and Mineral Resources (ESDM) in managing social media. Data collection techniques were carried out using interviews with research informants. The informants in this study were 2 people. The data analysis technique uses qualitative descriptive analysis which consists of data reduction, presentation and conclusions. The research results show that the creative strategy that can be carried out by the public relations of the Bengkulu Province ESDM Service in managing social media instagram@esdmprovbengkulu is based on the theory presented by Oktafiandi (2018:6) which consists of creative brief, massage objective. targeting and branching. For creative briefs, this can be done by paying attention to several steps before creating content, such as the fact-finding, planning, communication and evaluation stages. The message objective aspect is to pay attention to what message you want to convey so that the content created attracts the audience's attention. This can be done by editing photos and video content as attractive as possible. For the targeting aspect, the target in creating Instagram content is the community, while branting can be seen from increasing followers which can be done by carrying out activities that are beneficial to the community so that it can increase followers.